Preliminary Studies on the Vegetation of Kailana, Rajasthan - Bhimaya, C. P.; Cherian, A.; Satyanarayan, Y. (Indian Forester, 1964)
An ecological study of the vegetation of Kailana, a rocky area 7 miles from Jodhpur was carried out to assess changes in the composition and vegetative cover due to protection. Quantitative data was collected on the analytical characters of trees and shrubs and ground vegetation in different compartments fenced since 1953 to 1957. Comparative studies were made in the unprotected area. An over-all increase in the number of trees and shrubs was observed although succession of vegetation was slow. Of the planted species, Prosopis juliflora and Cassia auriculata have well established. Reduction in the number of some of regressive species like Euphorbia neriifolia and Capparis decidua have been observed. Development of trees and shrubs were found to be better in compartments having favourable micro-relief features. In the case of grasses, it was found that the regressive stage of Oropetium thomaeum-Tragus biflorus is being replaced by a higher perennial grass stage of Eleusine flagellifera-Dactyloctenium sindicum, the establishment being more successful in depressions. An increase in the number of weeds has also been observed in the protected compartments. It has been shown that micro-relief is an important factor in planning afforestation work in arid zone.